Eco-anxiety or simply eco-worry? Incremental validity study in a representative Spanish sample - Vecina, María Luisa; Alonso-Ferres, María; Díaz-Silveira, Cintia (Frontiers in Psychology, 2025)
Scientific literature is keen to promote the study of eco-anxiety despite its current low prevalence and inconsistent relationships with pro-environmental behavior and mental health. In this paper, we analyze in a representative sample of the Spanish population (N = 1911) the incremental validity of the eco-worry construct concerning that of eco-anxiety at three levels of environmental commitment: high (environmental activists), medium (people who are not part of any environmental organization but who would like to), and low (people who neither belong to environmental groups nor want to). Our results showed that (1) the environmental activists in our sample did not seem to be eco-anxious but rather eco-worried, and (2) at the three levels of environmental commitment, eco-worry but not eco-anxiety positively mediated the relationship between climate change perception and general willingness for environmental behavior, and eco-worry, but not eco-anxiety, positively connected with life satisfaction through the general willingness to behave pro-environmentally. It is concluded that eco-anxiety does not add anything to the more intuitive and non-pathological concept of eco-worry, except for the alarm signal, which is not at all strategic when the goal is to promote individual pro-environmental behaviors and collective social actions.